Defining desirable natural product derived anticancer drug space: optimization of molecular physicochemical properties and ADMET attributes - Deepika Singh (International Association of Physical Chemists (IAPC), 2016)
As part of our endeavor to enhance survival of natural product derived drug candidates and to guide the medicinal chemist to design higher probability space for success in the anti cancer drug development area, we embarked on a detailed study of the property space for a collection of natural product derived anti cancer molecules. We carried out a comprehensive analysis of properties for 24 natural products derived anti cancer drugs including clinical development candidates and a set of 27 natural products derived anti cancer lead compounds. In particular, we focused on understanding the interplay among eight physicochemical properties including like partition coefficient (log P), distribution coefficient at pH=7.4 (log D), topological polar surface area (TPSA), molecular weight (MW), aqueous solubility (log S), number of hydrogen bond acceptors (HBA), number of hydrogen bond donors (HBD) and number of rotatable bonds (nRot) crucial for drug design and  relationships between physicochemical properties, ADME (absorption, distribution, metabolism, and elimination) attributes, and in silico toxicity profile for these two sets of compounds. This analysis provides guidance for the chemist to modify the existing natural product scaffold or designing of new anti cancer molecules in a property space with increased probability of success and may lead to the identification of druglike candidates with favorable safety profiles that can successfully test hypotheses in the clinic.